Investigation of The Impact of Flood Spreading on The Biological Indices of Plants in The Kowsar Aquifer Station - Seyed Mohammad Reza Habibian; Elham Fakhimi (مدیریت بیابان)
Keywords: Biodiversity; Species richness; in recent years, flood-spreading systems have emerged as one of the most effective methods for land utilization in arid and semi-arid regions. These systems operate by directing excess water from rivers or reservoirs onto agricultural land, facilitating soil infiltration. This practice not only enhances soil moisture and improves crop yields but also mitigates flood-related hazards, raises groundwater levels, and rehabilitates degraded lands. The present study aimed to assess the impact of flood spreading on biological indicators specifically, species diversity, composition, richness, and uniformity to support vegetation restoration and land improvement in the arid and desert region of Garbaygan, Fasa.  This research was conducted in the Bisheh-Zard 1 flood-spreading network and a control plot (without flood spreading). Biological indicators (diversity, richness, uniformity, density, and species composition) were evaluated using a random-systematic sampling method along seven 150m transects. Six transects were placed within the Bisheh-Zard 1 flood-spreading network across six strips, while one transects was positioned in the control area. In each transect, 15 sample units of 2m2 were established at 10m intervals, yielding a total of 105 sample units collected in the spring of 2023. The biological types of species were classified according to Raunkiaer’s system in both flooded and control areas. Species richness and diversity were assessed using the Margalef and Menhinick indices, while the Shannon-Wiener and Simpson indices were applied to measure diversity. Uniformity was determined using Hill’s index. PAST software was utilized for the analysis of biological indices. The results revealed a statistically significant difference (p<0.01) in biodiversity indices including species diversity, richness, uniformity, density, and species composition between the strips within the Bisheh-Zard 1 flood-spreading network and the control area. These findings highlight the positive impact of flood-spreading systems on biodiversity and provide valuable insights for ecosystem management and land restoration strategies in arid environments.